1992
DOI: 10.1016/1044-0305(92)87055-4
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray mass spectrometry: a study on some aqueous solutions of metal salts

Abstract: Aqueous metal salt solutions were used as models to probe the origin of the species observed in the electrospray mass spectrum. A qualitative or semiquantitative correlation among different species was observed between electrospray responses and calculated equilibrium aqueous solution concentrations. Quantitative correlations were obtained, however, when ions that were identical in charge and similar in type were selected for comparison. In these experiments the ions experienced very similar electrospray-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(98 citation statements)
references
References 18 publications
5
93
0
Order By: Relevance
“…Although they did not mention the possibility of studying systems under equilibrium, they proposed the use of this technique for ''the analysis of ionic transition-metal complexes.'' The authors who first underlined the possible application to metal-ligand equilibrium studies were Cheng et al (1992) and Gall et al (1992). After them, an increasing number of authors used ESI-MS for this purpose (see Fig.…”
Section: Applications To Metal-ligand Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they did not mention the possibility of studying systems under equilibrium, they proposed the use of this technique for ''the analysis of ionic transition-metal complexes.'' The authors who first underlined the possible application to metal-ligand equilibrium studies were Cheng et al (1992) and Gall et al (1992). After them, an increasing number of authors used ESI-MS for this purpose (see Fig.…”
Section: Applications To Metal-ligand Systemsmentioning
confidence: 99%
“…Several authors considered the ion response factors to be roughly equivalent for all the species in solution (Wang & Gokel, 1996;Goolsby et al, 1999;Reany et al, 2000;Ross, Ikonomou, & Orians, 2000a;Moulin et al, 2001;Colette et al, 2002;Jacopin et al, 2003) or for part of them (Cheng et al, 1992). (g) Finally, high concentrations of supporting electrolyte cannot be used in ESI-MS, because the signal of the analyte ions would be suppressed in the presence of high concentrations of other electrolytes (Smith et al, 1993;.…”
Section: Other Problemsmentioning
confidence: 99%
“…For selection of an appropriate analytical technique, responsiveness is one of the critical parameters for the quantitation of chemical compounds [1]. ESI response in particular can vary significantly among different analytes that have identical solution concentrations [26]; thus, different solute ionization efficiency can result in apparent responses that differ by > 3 orders of magnitude despite equimolar concentrations in solution [7]. Besides fundamental interests such as the suitability of ESI for the analysis of a particular analyte, data on molar responses can also provide general usefulness in analytical method development such as understanding the underlying mechanisms enabling the selection of optimal instrumental parameters, deducing molecular characteristics of an unknown species or information on the feasibility of calibration without chemical standards [7].…”
Section: Introductionmentioning
confidence: 99%
“…The usefulness of ESI-MS results for interpretation or prediction of actual solution conditions is also under ongoing debate, [26] and several studies have proposed the quantitative correlation of observed phenomena with ESI-MS gas-phase studies to actual solution conditions. [27][28][29] Recently, Park et al reported the ESI-MS structural characterization of several transition metal ion complexes formed with alachlor, an organochlorine pesticide, with the conclusion that in that case the transition metal ions exert their catalytic activity via an insertion mechanism into the C-Cl bond followed by Cl elimination. [30] The importance of OPs in agriculture and the scarcity of information currently available on associated OP degradation mechanisms induced by transition metal ion catalyzed complexation led us to carry out a study of the structural features of OP-transition metal ion complexes in solution with ESI-MS/MS, complementing our previous kinetic degradation studies, employing Ag + , Cu 2+ and Hg 2+ as examples.…”
mentioning
confidence: 99%